Comparison of nutritional status and dietary habits among student athletes and non-student athletes of UiTM / Intan Nursyazanie Mohamad Rizal and Siti Soraya Mohd Elias - Mohamad Rizal, Intan Nursyazanie; Mohd Elias, Siti Soraya (Universiti Teknologi MARA, 2021)
The purpose of this study was to compare nutritional status and dietary habits among student athletes and non-student athletes of UiTM as well to study the relationship between the body mass index (BMI), dietary habits and nutritional status. An online questionnaire was used to collect data of respondents. Dietary habits questionnaire was modified from Marino (2001) which comprised 18 questions. Nutrition knowledge questionnaire was modified from Paugh (2005) which comprised of 29 questions. There was a significant difference in total dietary habits score between student athletes and non-student athletes, t (198) = -3.145, p = 0.002 meanwhile, there was no significant difference in total nutrition knowledge score between student athletes and non-student athletes, t(198)=0.334, p=0.433. Null hypothesis accepted for both student athletes and non-student athletes, showing that their BMI did not have significant relationship with their dietary habits and nutrition knowledge. The mean dietary habits score of student athletes were higher than non-student athletes, so there was a significant difference in total dietary habits score between two groups. Meanwhile, there was no huge difference between the mean score for nutrition knowledge between student athletes and non-student athletes. There was no significant difference in total nutrition knowledge score between the two groups.